2014
DOI: 10.2169/internalmedicine.53.1381
|View full text |Cite
|
Sign up to set email alerts
|

Perivasculitic Panencephalitis with Relapsing Polychondritis: An Autopsy Case Report and Review of Previous Cases

Abstract: We herein report an autopsy case of relapsing polychondritis encephalitis coexisting with a Lewy body pathology and also review previous autopsy cases. A 59-year-old man exhibited a tremor of the right hand, small-steppage gait and bradykinesia. Five years later, he presented with relapsing auricular chondritis and scleritis and subsequently showed exacerbation of extrapyramidal symptoms. A histological examination revealed perivascular lymphocytic cuffing and infiltration in the small vessels, as well as loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Meningitis and enephalitis in RP can show various symptoms like cognitive impairment, psychomotor abnormality, confusion, and disorientation ( 8 ). Characteristic MRI pattern has not been established but multifocal hyper-intensity lesions, especially in basal ganglia and periventricular and subcortical white matter are the most common findings ( 7 9 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meningitis and enephalitis in RP can show various symptoms like cognitive impairment, psychomotor abnormality, confusion, and disorientation ( 8 ). Characteristic MRI pattern has not been established but multifocal hyper-intensity lesions, especially in basal ganglia and periventricular and subcortical white matter are the most common findings ( 7 9 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Subclinical brain MRI abnormality has not been reported in RP. Autopsy studies of RP patients with symptomatic CNS involvement have shown meningoencephalitis, vasculitis, or encephalitis with perivascular inflammatory cells . Anti‐neutral glycosphingolipid antibodies are found specific in RP patients with encephalitis and may be related to the pathophysiology, which was absent in our patient.…”
Section: Discussionmentioning
confidence: 46%
“…Autopsy studies of RP patients with symptomatic CNS involvement have shown meningoencephalitis, vasculitis, or encephalitis with perivascular inflammatory cells. 6 Anti-neutral glycosphingolipid antibodies are found specific in RP patients with encephalitis and may be related to the pathophysiology, 5,7 which was absent in our patient. The reason why the MRI abnormality in our patient caused no or very mild CNS symptoms are unknown, but the FLAIRhigh lesions may have largely been vasogenic edema associated with perivascular inflammation, which is consistent with contrast enhancement restricted to the perivascular space, increased ADC in the acute phase of lesion enlargement, and the improvement of FLAIR-high lesions without atrophy.…”
Section: Discussionmentioning
confidence: 50%
“…[29][30][31] Moreover, an increasing body of evidence has revealed pathological presentations of vasculitis and inflammatory changes-such as T-cell infiltration, panencephalitis, and granuloma formation-in RP patients. [32][33][34][35][36] In our study, the incidence of ear involvement was higher in RP patients with CNS involvement compared with RP patients without CNS involvement. The involvement of the eyes and heart was correlated with RP patients with CNS involvement, after the factors sex and the admission age were controlled.…”
Section: Discussionmentioning
confidence: 86%